2017
DOI: 10.1111/hdi.12582
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of target weight based on absolute blood volume reduces the frequency of intradialytic morbid events

Abstract: Adjustment of target weight based on information of Vs, Vo, and IME appears as a feasible approach to reduce the frequency of IME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 32 publications
3
53
0
3
Order By: Relevance
“…In a pilot study, an absolute BV below 65 mL/kg was found to predict intra-dialytic morbid events in 10 out of 12 patients [10]. Absolute BV was more predictive for intra-dialytic morbid events than pre-dialytic OH assessed by BIS [63]. Previously, it was also observed that vena cava diameter, which is also related to intravascular volume, predicted treatment tolerance in an intensive care setting [64].…”
Section: Can Technology Aid the Clinical Decision Process?mentioning
confidence: 87%
“…In a pilot study, an absolute BV below 65 mL/kg was found to predict intra-dialytic morbid events in 10 out of 12 patients [10]. Absolute BV was more predictive for intra-dialytic morbid events than pre-dialytic OH assessed by BIS [63]. Previously, it was also observed that vena cava diameter, which is also related to intravascular volume, predicted treatment tolerance in an intensive care setting [64].…”
Section: Can Technology Aid the Clinical Decision Process?mentioning
confidence: 87%
“…Online measurement of Hct and Hb in the extracorporeal circulation is currently used to track the degree of UF‐induced hemoconcentration during hemodialysis. Recently, Schneditz et al and Kron et al demonstrated that the dilution of blood and the calculated increase in relative blood volume (in %) caused by the infusion of ultrapure dialysate can be used to determine the absolute blood volume (V b , in ) at the time of infusion as: Vb=normalVbolusRBVPostRBVPre.110 where V bolus is the volume of the dialysate bolus (in mL), and RBV Pre and RBV Post refer to the relative blood volume (in %) before and after infusion.…”
Section: Methodsmentioning
confidence: 99%
“…Oberhalb von 65 ml/kg wurden bei kei-nem Patienten intradialytische Komplikationen beobachtet. Andererseits blieben nur 4 von 19 Patienten bei einem Blutvolumen von unter 65 ml/kg stabil [17]. Somit scheint ein absolutes Blutvolumen von etwa 65 ml/kg eine kritische Grenze für das Auftreten von volumenbedingten Komplikationen während der Dialyse darzustellen [16,17].…”
Section: Absolutes Blutvolumen Und Komplikationenunclassified